The Effect of Guided Inquiry Learning Model on Process Skills Science and Students' Higher-Level Thinking Skills on Heat and Transfer Themes of Class V SD Negeri 104260 Melati - Ahmad Marwan; Hasruddin Hasruddin; Yusnadi Yusnadi (BIRCU, 2021)
This research aims to determine the effect of guided inquiry learning models on science process skills and higher order thinking skills on the theme of heat and its displacement in grade V SD Negeri 104260 Melati. The research instrument included observation of science process skills and tests of higher order thinking skills. This study uses the analysis of the Independent Sample Test (t test).The average value of science process skills in the guided inquiry class was 81.62 and the direct instruction learning model class was 79.02. A significant influence on students' science process skills in the learning process on the theme of heat and its displacement, with a score of tcount (2.384)> ttable (2.004) for n = 56, α = 0.05 and sig. 2 tailed (0.021) <α = 0.05, so that H₀rejected. then Ho was rejected and Ha accepted. The average value of high-order thinking skills in the guided inquiry class is 75.57 and in the class of direct instruction learning model. A total of 67.43. The results of the analysis of high-order thinking skills have tcount (3.597)> ttable (2.004) for n = 56, α = 0.05 and sig. 2 tailed (0.001) <α = 0.05, so that H₀rejected and Ha accepted. Guided inquiry learning model affects science process skills and high-order thinking skills of students on the theme of heat and its displacement in grade V SD Negeri 104260 Melati.